Voltage-Dependent Inhibition of Glycine Receptor Channels by Niflumic Acid - Maleeva, Galyna; Peiretti, Franck; Zhorov, Boris S.; Bregestovski, Piotr (Frontiers in Molecular Neuroscience, 2017)
Niflumic acid (NFA) is a member of the fenamate class of nonsteroidal anti-inflammatory drugs. This compound and its derivatives are used worldwide clinically for the relief of chronic and acute pain. NFA is also a commonly used blocker of voltage-gated chloride channels. Here we present evidence that NFA is an efficient blocker of chloride-permeable glycine receptors (GlyRs) with subunit heterogeneity of action. Using the whole-cell configuration of patch-clamp recordings and molecular modeling, we analyzed the action of NFA on homomeric α1ΔIns, α2B, α3L and heteromeric α1β and α2β GlyRs expressed in CHO cells. NFA inhibited glycine-induced currents in a voltage-dependent manner and its blocking potency in α2 and α3 GlyRs was higher than that in α1 GlyR. The Woodhull analysis suggests that NFA blocks α1 and α2 GlyRs at the fractional electrical distances of 0.16 and 0.65 from the external membrane surface, respectively. Thus, NFA binding site in α1 GlyR is closer to the external part of the membrane, while in α2 GlyR it is significantly deeper in the pore. Mutation G254A at the cytoplasmic part of the α1 GlyR pore-lining TM2 helix (level 2’) increased the NFA blocking potency, while incorporation of the β subunit did not have the significant effect. The Hill plot analysis suggests that α1 and α2 GlyRs are preferably blocked by two and one NFA molecules, respectively. Molecular modeling using Monte Carlo energy minimizations provides the structural rationale for the experimental data and proposes more than one interaction site along the pore where NFA can suppress the ion permeation.